An Analysis Of Teachers’ Perspectives on the Use of Google Classroom to Enhance Assessment for Learning in Accounting - Thabiso Jonah Motsoeneng; Wellington Manzi; Boitumelo Moreeng (E-Journal of Humanities, Arts and Social Sciences, 2023)
The introduction of educational technology has transformed the assessment practices of Accounting teachers. The advent of technology has created space for Accounting teachers to design meaningful Assessment for Learning (AfL) tasks using technology platforms such as Google Classroom. Google Classroom can be used to create meaningful learning environments that facilitate the development of the necessary 21st-century skills and competencies such as critical thinking, problem-solving, self-management and self-competence. However, nearly a decade after its introduction, Google Classroom is still minimally used in South African schools. This empirical study, therefore, explored the use of Google Classroom to enhance AfL in Accounting. The study used a qualitative research approach and Participatory Action Research as a research design to explore the use of Google Classroom as an AfL technique by Accounting teachers. As with other qualitative studies, focus group discussions were used to generate data from four purposefully selected Accounting teachers. Data was analysed using thematic analysis. The findings revealed that Accounting teachers perceived Google Classroom to be an assessment technique which leads to effective teaching and learning because it provides a platform for learner active participation. Furthermore, the teachers displayed an interest in Google Classroom as a tool to facilitate meaningful teaching and learning, which enabled them to support and strengthen the learning of Accounting. It is recommended that teachers constantly use this platform as it allows learners to be assessed outside the boundaries of a physical classroom.